Challenges and perspectives to enhance cattle production via in vitro techniques: focus on epigenetics and cell-secreted vesicles - Fabiana Fernandes Bressan; Paulo Fantinato-Neto; Gabriella Mamede Andrade; Juliano Rodrigues Sangalli; Rafael Vilar Sampaio; Juliano Coelho da Silveira; Felipe Perecin; Flávio Vieira Meirelles (Ciência Rural, 2015)
This review aim to present some clinical problems found in IVP-derived animals focusing on NT procedures and to discuss the possible role of epigenetics in such process. Also, as cell-secreted vesicles have been reported as possible regulators of important physiological reproductive processes such as folliculogenesis and fertilization, it is also presented herein a new perspective of manipulating the pre-implantation period trough effector molecules contained in such vesicles.